A Monist View of Quantum Theory and Neuroscience - Pereira Jr, Alfredo [UNESP] (Springer Nature, 2019)
In this commentary to Henry Stapp’s target paper, I defend a view alternative to both von Neumann’s methodological Dualism, and Stapp’s choice of Idealist metaphysics. I argue for a Monist metaphysical thesis, claiming that the observed physical systems and the observers who study them originate from a common “neutral” source (neither material nor mental). Scientifically, I argue for an epistemological view of the neurosciences in which the brain/mind system has a circular topology, affording conscious experiences. In this Monist view of the brain/mind, the decoherence process is not fully completed, as in the “mental collapse” view: there is a “recoherence” process in living tissue that generates conscious episodes experienced by the organisms.
Keywords: Monist view; Neuroscience; Neutral monism; Quantum theory; Recoherence